EFEKTIVITAS PEMBERIAN KAPULAGA JAHE DALAM MENGURANGI FREKUENSI MUAL MUNTAH PADA IBU HAMIL TRIMESTER PERTAMA DI DESA SUKA RAYA - Hadya, Rizca Annur; Sulaiman, Sulaiman (Yayasan Nuraini Ibrahim Mandiri, 2024)
Nausea and vomiting are most common in the first trimester of pregnancy, but about 12% of pregnant women continue to experience them up to 9 months. Nausea and vomiting are part of the normal spectrum of pregnancy, hyperemesis is considered an extreme condition. This study aims to evaluate the effect of Kajah ( Cardamom-Ginger) Pudding on reducing the frequency of nausea and vomiting in first trimester pregnant women. This study used a quasi-experimental design with a pretest-posttest approach on 10 pregnant women who experienced nausea and vomiting. The respondents were divided into two groups: an intervention group that received Kajah pudding and a control group that did not receive the intervention. The results showed that consumption of Kajah pudding significantly reduced the frequency of nausea and vomiting in first trimester pregnant women compared to the control group (p < 0.05). Kajah pudding may be an effective natural alternative in overcoming nausea and vomiting during the first trimester of pregnancy.